A Stylistic Analysis of Travel News About Indonesia at CNN Website - Alfi Rizki Maulidiyah (Jurnal Linguistik Terapan, 2020)
This research discovered some stylistic features of travel news about Indonesia at the CNN website and grouped them into: graphological levels, syntactic levels, and semantic levels. Graphological levels are about the physical appearance of the news and punctuation. The news had the same pattern of physical appearance. The punctuation employed in this news included quotation marks, em dashes, colon, apostrophe, hyphens, and parentheses. Syntactic levels are about sentence types. The most common sentence types were simple sentences and complex sentences. Semantic levels talk about rhetorical devices. The news had some rhetorical devices, such as parenthesis, simile, metaphor, litotes, personification, metaphor, synecdoche, metonymy, and onomatopoeia.